Standard versus Minimally Invasive Transforaminal Lumbar Interbody Fusion: A Prospective Randomized Study. (15th June 2017) - Serban, Daniel; Calina, Niki; Tender, Gabriel
Abstract : Symptomatic spondylolisthesis patients may benefit from surgical decompression and stabilization. The standard (S) technique is a transforaminal lumbar interbody fusion (TLIF). Newer, minimally invasive (MI) techniques seem to provide similar results with less morbidity. We enrolled patients with at least 6 months of symptoms and image-confirmed low-grade spondylolisthesis, at a single academic institution, between 2011 and 2015. The patients were randomized to either S or MI TLIF. The primary outcome measure was the Oswestry Disability Index (ODI) improvement at 1 year. Secondary outcome measures included length of operation, estimated blood loss, length of hospitalization, and fusion rates at 1 year. Forty patients were enrolled in each group. The differences in mean operative time and estimated blood loss were not statistically significant between the two groups. The patients were discharged after surgery at 4.12 days for the S TLIF group and 1.92 days for the MI TLIF group. The ODI improvement was similar and statistically significant in both groups. The fusion was considered solid in 36 (90%) of patients at 1 year in both groups. In conclusion, the two techniques provided similar clinical and radiological outcomes at 1 year. The patients undergoing MI TLIF had a shorter hospital stay. This trial is registered with NCT03155789 .